Evaluation of shear strength of single lap joint - Abul Haziq, Ahmad Foaad (Universiti Malaysia Sarawak, UNIMAS, 2008)
Adhesive Bonding has become more useful in today’s technology. The advantages of adhesive bond from other joining method such as welding have made adhesive bond become more demanding. Adhesives bonding have been use in aircraft, space structure and automotive industries. Because of the use of adhesive bonding has become more demanding, it is important for a research to find the shear strength of adhesive bonding. In this research, the testing was done to find the effect of different surface geometry on the bond strength. To obtain the shear strength values, testing were conduct on adhesive bonding according to America Society for Testing Material (ASTM) D- 1001 standard. In this project, the testing also involves using different type of adhesive and different surface geometry. There are five different type of surface geometry that will be tested. The specimens were fabricated to achieve the required geometry. After that, it will go through surface preparation. The testing was conducted after it has gone through all the process mention before.